Implementasi Mitologi dan Simbol Ganesha dalam Budaya Kontemporer Masyarakat Bali - Agus Sumarpin Giri; I Gede Suwantana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Culture and mythological narratives about Ganesha are inherent in the life of the Hindu community in Bali, but have undergone various changes along with the pace of civilization. Evidently, Ganesha as one of the sacred symbols is widely used in various life interests of modern society, which has no relevance to the sacred context. This paper analyzes the implementation of Ganesha's symbolic mythology in the contemporary cultural space of Balinese society. Mythologically, Ganesha is believed to be the son of Shiva who has the power to overcome all obstacles. This mythology is contained in the attributes of Ganesha which have a symbolic meaning. The full embodiment of the Ganesha symbol in the modern era is widely implemented in the contemporary culture of Balinese life, both in the fields of architecture, aesthetics (art), social organization, including economic life. This work is expected to be a reference for fostering a critical and selective culture when using the Ganesha symbol in various aspects of Balinese life.